A HOLISTIC APPROACH OF AMNESTY APPLICATION FOR BAIQ NURIL MAKNUN IN THE FRAMEWORK OF CONSTITUTIONAL LAW OF INDONESIA - Reda Manthovani (Yustisia, 2019)
The Supreme Court has rejected a petition for case review from Baiq Nuril Maknun, a West Nusa Tenggara woman who was convicted of defamation against her alleged sexual harasser. Justices Margono, Desniyati and Suhadi rejected Nuril’s challenge against the Supreme Court's decision in September 2018, which found Nuril guilty of violating Article 27 of the Electronic Information and Transactions (ITE) Law and sentenced her to six months in prison and a fine of Rp 500 million (US$34,644). The defamation case has been criticized for using the controversial law to incriminate an alleged victim of sexual harassment, when the Mataram Education Agency reported Nuril for recording the phone call.This research is prescriptive normative research namely, legal research that takes legal issues as a norm system used to provide prescriptive justifications about a legal event. From Nuril’s case we can see the laws are sorely inadequate, case in point the Electronic Information and Transactions Law (ITE Law), that got her into trouble. It’s so rubbery, it can be interpreted any way anyone wants. Amnesty should be given to Baiq Nuril Maknun because amnesty is the authority of the President for the interests of the state, in this case human rights and citizens' rights to get legal protection and free from discrimination and Law Number 11 Drt In 1954, yet it contradicted the constitution in cases and institutions, because Article 14 paragraph (2) of the 1945 Constitution of the Republic of Indonesia had no case restrictions in granting amnesty and was carried out with consideration of the People’s Representative Council of The Republic of Indonesia.